2011
DOI: 10.1590/s1516-35982011000800005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil fermentativo de silagens de cana-de-açúcar in natura ou queimada e tratadas ou não com Lactobacillus buchneri

Abstract: IntroduçãoEm confinamentos, a cana-de-açúcar é um dos volumosos mais utilizados na alimentação de ruminantes, devido à alta produtividade de energia por área. Todavia, o risco de incêndios acidentais pode comprometer o uso da cana-de-açúcar fresca. Neste caso, a ensilagem poderia ser utilizada não somente como prevenção, mas também como solução. Em estudo pioneiro sobre os efeitos do fogo na ensilagem da cana-de-açúcar, Bernardes et al. (2007) constataram que silagens de cana-de-açúcar queimada apresentam maio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…The negative effect of lignin on digestibility has been previously documented (Jung and Allen, 1995). However, all silages had low digestibility (435-490 g/kg of organic matter), and our data are in accordance with previous studies (Roth et al, 2010;Siqueira et al, 2011b), which also reported a low digestibility of burned sugarcane silages.…”
Section: Trial Isupporting
confidence: 93%
“…The negative effect of lignin on digestibility has been previously documented (Jung and Allen, 1995). However, all silages had low digestibility (435-490 g/kg of organic matter), and our data are in accordance with previous studies (Roth et al, 2010;Siqueira et al, 2011b), which also reported a low digestibility of burned sugarcane silages.…”
Section: Trial Isupporting
confidence: 93%
“…Anim., Salvador, v.21, 01 -13, e210212020, 2020 ISSN 1519 9940 http://dx.doi.org/10.1590/S1519-9940210212020 Balieiro et al (2009). Siqueira et al (2011) found values of 24.8 % and 25.9 % DM for silage containing L. buchneri and silages without inoculants, respectively. There was no significant difference (P > 0.05) for crude protein contents.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, a silage pH below 4.2 may have inhibited bacterial growth and propionic acid production (Michel et al, 2017). Siqueira et al (2011) evaluated fresh sugarcane silage (without burning) and burned with calcium oxide (CaO) and / or L. buchneri, and observed an NDF content of 75.9 % for sugarcane silage with added L. buchneri at 60 days of fermentation, which was higher than the content of the material before ensiling. This anomaly was also observed in the present study, where sugarcane had a lower NDF content before ensiling (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation